2008
DOI: 10.1002/mnfr.200700380
|View full text |Cite
|
Sign up to set email alerts
|

Food bioactives, apoptosis, and cancer

Abstract: Apoptosis interchangeably referred to as programmed cell death is a key pathway for regulating homeostasis and morphogenesis of mammalian cells and is connected with several diseases, in particular, cancer. It is widely believed that misregulation of this pathway leads to the development of cancer. Reflecting this knowledge, the mechanism of action for many currently used anticancer agents were specifically targeted to regulate the apoptotic pathway further stressing the role of programmed cell death in mainta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
71
0
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 78 publications
3
71
0
6
Order By: Relevance
“…In vivo , formononetin induced a dramatic decrease in tumor weight in the treated mice, further confirming the potential application of formononetin in treating human prostate cancer. A lot of studies demonstrated that the underlying mechanism of dietary phytochemicals-mediated chemopreventive activity may involve the induction of cell cycle arrest [22,23]. In accordance with the previous studies, increased cell cycle arrest at G0/G1 phase was found in formononetin-treated human prostate cancer cells, which suggests that the induction of cell cycle arrest may be the major mechanism for its anti-proliferation effect.…”
Section: Discussionsupporting
confidence: 75%
“…In vivo , formononetin induced a dramatic decrease in tumor weight in the treated mice, further confirming the potential application of formononetin in treating human prostate cancer. A lot of studies demonstrated that the underlying mechanism of dietary phytochemicals-mediated chemopreventive activity may involve the induction of cell cycle arrest [22,23]. In accordance with the previous studies, increased cell cycle arrest at G0/G1 phase was found in formononetin-treated human prostate cancer cells, which suggests that the induction of cell cycle arrest may be the major mechanism for its anti-proliferation effect.…”
Section: Discussionsupporting
confidence: 75%
“…The 4 0 -O-methyl derivative of genistein, biochanin A that is a major isoflavone constituent in red clover (Trifolium pratense), has also been reported to possess cytotoxic properties against cancer cells [11]. Various other polyphenolic compounds such as flavonoids, tannins, curcuminoids, gallocatechins, stilbenes, and anthocyanidins have been implicated as chemopreventive agents [12]. However, the mechanism by which these compounds inhibit proliferation and induce apoptosis in cancer cells has been the subject of considerable interest.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that these foods contain many 'bioactive' compounds, which both in vitro and in vivo have profound effects on the behaviour of cancerous cells. Some of these effects include increasing rates of apoptosis, decreasing incidences of metastasis and arresting the cell cycle [Liu et al, 2007;Gallo et al, 2008;Pan et al, 2008].One food which has demonstrated many 'bioactive' properties is the American cranberry (Vaccinium macrocarpon). The phenolic constituents of cranberry fruit include anthocyanins, flavonols, polyflavan-3-ols (proanthocyanidins-PACs) and phenolic acid derivatives.…”
mentioning
confidence: 99%